2021
DOI: 10.3390/v13050897
|View full text |Cite
|
Sign up to set email alerts
|

Cascading from SARS-CoV-2 to Parkinson’s Disease through Protein-Protein Interactions

Abstract: Extensive extrapulmonary damages in a dozen of organs/systems, including the central nervous system (CNS), are reported in patients of the coronavirus disease 2019 (COVID-19). Three cases of Parkinson’s disease (PD) have been reported as a direct consequence of COVID-19. In spite of the scarce data for establishing a definitive link between COVID-19 and PD, some hypotheses have been proposed to explain the cases reported. They, however, do not fit well with the clinical findings reported for COVID-19 patients,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 124 publications
0
20
0
Order By: Relevance
“…Another preprint study analyzing infection by SARS-CoV-2 in macaques found the formation of Lewy bodies ( 138 ). These plaques, which are predominantly composed of alpha-synuclein, are associated with the pathology of Parkinson’s disease and have been hypothesized to derive from a viral etiology including influenza A, norovirus and others ( 139 141 ). In a preprint, data from autopsies corroborated the presence of SARS-CoV-2 in all lobes of the brains of COVID-19 patients although there was a lack of inflammation ( 142 ).…”
Section: Neurological Symptoms Of Covid-19mentioning
confidence: 99%
“…Another preprint study analyzing infection by SARS-CoV-2 in macaques found the formation of Lewy bodies ( 138 ). These plaques, which are predominantly composed of alpha-synuclein, are associated with the pathology of Parkinson’s disease and have been hypothesized to derive from a viral etiology including influenza A, norovirus and others ( 139 141 ). In a preprint, data from autopsies corroborated the presence of SARS-CoV-2 in all lobes of the brains of COVID-19 patients although there was a lack of inflammation ( 142 ).…”
Section: Neurological Symptoms Of Covid-19mentioning
confidence: 99%
“…Molecular investigations have established links between COVID-19 and PD focusing on protein interactions. In all, 44 proteins in the CNS implicated in PD were found to interact with 24 host proteins from the lung that interact with SARS-CoV-2 viral proteins [ 106 ]. The two most promising interaction candidates were Rab7a and NUP62 [ 106 ].…”
Section: Chaptermentioning
confidence: 99%
“…In all, 44 proteins in the CNS implicated in PD were found to interact with 24 host proteins from the lung that interact with SARS-CoV-2 viral proteins [ 106 ]. The two most promising interaction candidates were Rab7a and NUP62 [ 106 ]. Rab7a is a lysosomal protein reducing the proportion of cells with α-synuclein particles as well as the toxicity of α-synuclein, whereas NUP62 is involved in autophagosome formation [ 106 ].…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the lack of detected viral gene expression in the CNS casts doubt on the hypothesis that the cytokine storm is causing or leading contributor to the neurological damage and neuropsychiatric symptoms seen in some SARS-CoV-2 cases. Exosomes have been previously reported to aid in viral pathogenesis ( Estrada, 2021 ).…”
Section: Introductionmentioning
confidence: 99%